Quasi-two-dimensional α-molybdenum oxide thin film prepared by magnetron sputtering for neuromorphic computing. Issue 28 (15th June 2022) - Wu, Zhenfa; Shi, Peng; Xing, Ruofei; Xing, Yuzhi; Ge, Yufeng; Wei, Lin; Wang, Dong; Zhao, Le; Yan, Shishen; Chen, Yanxue
Abstract : An all-solid-state synaptic transistor with about 4 orders conductance modulation is fabricated based on the α-MoO3 thin film. A three-layer artificial neural network with high recognition accuracy was constructed based on this synaptic transistor. Abstract : Two-dimensional (2D) layered materials have attracted intensive attention in recent years due to their rich physical properties, and shown great promise due to their low power consumption and high integration density in integrated electronics. However, mostly limited to mechanical exfoliation, large scale preparation of the 2D materials for application is still challenging. Herein, quasi-2D α-molybdenum oxide (α-MoO3 ) thin film with an area larger than 100 cm 2 was fabricated by magnetron sputtering, which is compatible with modern semiconductor industry. An all-solid-state synaptic transistor based on this α-MoO3 thin film is designed and fabricated. Interestingly, by proton intercalation/deintercalation, the α-MoO3 channel shows a reversible conductance modulation of about four orders. Several indispensable synaptic behaviors, such as potentiation/depression and short-term/long-term plasticity, are successfully demonstrated in this synaptic device. In addition, multilevel data storage has been achieved. Supervised pattern recognition with high recognition accuracy is demonstrated in a three-layer artificial neural network constructed on this α-MoO3 based synaptic transistor. This work can pave the way for large scale production of the α-MoO3 thin film for practical application in intelligent devices.